2021
DOI: 10.1007/s00784-021-04256-1
|View full text |Cite
|
Sign up to set email alerts
|

Apical approach in periodontal reconstructive surgery with enamel matrix derivate and enamel matrix derivate plus bone substitutes: a randomized, controlled clinical trial

Abstract: Objectives This parallel, randomized controlled clinical trial evaluated the influence of bone substitutes (BS) on the efficacy of the non-incised papillae surgical approach (NIPSA) with enamel matrix derivate (EMD) in resolving deep, isolated, combined non-contained intrabony and supra-alveolar periodontal defects, preserving the soft tissue. Material and methods Twenty-four patients were randomized to treatment with NIPSA and EMD or NIPSA plus EMD and BS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 63 publications
0
22
0
Order By: Relevance
“…Figure 2 displays the relationships between the existing treatment arms (e.g., xenogeneic BG + EMD) from which the additive model was based upon. One‐hundred and twenty‐two treatment arms employed EMD 13 , 18,19,39,49,50,67,70,73,75–77,79,82,84–86,89,90,93,94,96–99,102,105–109 , 112–116,121–123,125,126,130,136–138,140–142,146,151,153,156–158,160,167–169,175 , 177,178,180,182–195,200–202,205–207,209–212 ,. 12 used rhPDGF‐BB 17,129,133,139,148,152,155,181 , 43 included PRF 19,71,72,74,78,80,81,83 , 88,91,92,103,110,115,120,131,144,145,149,150,154,162–165,170–174,196–198,203,204 , and 31 used PRP 68,87,95,100,101,117–119,124,127,128,132,134,135,143,147 , 159,161,166,173,174,179,199 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2 displays the relationships between the existing treatment arms (e.g., xenogeneic BG + EMD) from which the additive model was based upon. One‐hundred and twenty‐two treatment arms employed EMD 13 , 18,19,39,49,50,67,70,73,75–77,79,82,84–86,89,90,93,94,96–99,102,105–109 , 112–116,121–123,125,126,130,136–138,140–142,146,151,153,156–158,160,167–169,175 , 177,178,180,182–195,200–202,205–207,209–212 ,. 12 used rhPDGF‐BB 17,129,133,139,148,152,155,181 , 43 included PRF 19,71,72,74,78,80,81,83 , 88,91,92,103,110,115,120,131,144,145,149,150,154,162–165,170–174,196–198,203,204 , and 31 used PRP 68,87,95,100,101,117–119,124,127,128,132,134,135,143,147 , 159,161,166,173,174,179,199 .…”
Section: Resultsmentioning
confidence: 99%
“…The outcomes of flap procedures alone were reported in 54 study arms 18,39,49,70,72,74,76,78,80 , 82,84,86,87,89–92,94,105–109,113,121,128,131,149,152,158,163,164,169–173,175,177 , 178,190,195,198,200,203–205,210,212 . A total of 88 studies utilized BGs 17,19,49,50,67–71,75–78,80,81,83,84,86–88,91,94,95,97–102,104,110–112 , 114,116–120,122–124,126,127,129,130,132–135,137–148,150,153–157,159,161,164,166 , 167,170,174,179–181,187,192,193,196,197,199,206,208,209,211 , with 7 having utilized an autogenous BG 19,70,110,114,119,150,209 , 16 an allograft 67–69,77,78,81,88,116,123,124,135,147,156,157,166,197 , 28 a xenograft…”
Section: Resultsmentioning
confidence: 99%
“…The primary difference/variable from the conventional approach was that microsurgical technology increased visual and tactile perception. [ 35 36 37 ] The coarseness of most surgical manipulations is revealed when periodontal surgery is studied under a microscope. Tissue handling that appears to be delicate turns out to be gross crushing and tearing.…”
Section: Discussionmentioning
confidence: 99%
“…153,162,211,224,240 When tissue engineering strategies were tested against biologic agents alone for the treatment of infrabony defects, nine studies exhibited significantly higher outcomes in the tissue engineering strategy group, and another nine trials showed similar results. 155,162,180,187,205,210,212,221,235 Regarding furcation defects, two studies did not observe benefits in favor of tissue engineering strategies compared with conventional treatments, 220,223 but one trial obtained a statistically significantly superior clinical attachment level gain and pocket depth reduction after 1 year for mandibular furcations treated with tissue engineering strategies compared with guided tissue regeneration and flap alone. 185 The tissue engineering strategy group was also the treatment with the highest number of cases presenting complete closure of the furcation defect at 1 year.…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%
“…I, J, Flap closure. K, L, Clinical and radiographic outcomes at the 11-year follow-up 48,251,[151][152][153][158][159][160]1,[193][194][195][212][213][214][215][216][217][218][240][241][242][243]67-69 54 trials were as signed an unclear risk of bias, 31,33,61,63,64,71,79,87,101,161,163, 172,174,175, 178,179,181,183,185,192,198,208, 209,227,230,231,234,235,242,243,246,148-150,154-157, 166-169,201-205,219-221,223-226 and the remaining seven studies showed a high risk of bias. 171,184,196,236,237,249,250 1.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%